PENGEMBANGAN SISTEM INFORMASI MAHASISWA KULIAH KERJA NYATA (KKN) UNIVERSITAS PAPUA MENGGUNAKAN PHP DAN MYSQL: INFORMATION SYSTEM DEVELOPMENT REAL WORK COLLEGE STUDENTS (KKN) PAPUA UNIVERSITY USES PHP AND MYSQL - Kristia Yuliawan; Adie Purnama Putra (JISTECH: Journal of Information Science and Technology, 2018)
KKN is a form of academic activities related to community service activities that arecarried out by interdisciplinary and intraculicular activities. The implementation iscoordinated by research institutions and community service (LPPM). Data from PapuaState University students who have been modest so far, besides that there is no digitallyrecorded data, in the form of student numbers, student names, location of assignmentsor supervision. So there needs to be a MySQL database application that can facilitateLPPM and help students in the KKN registration process.The research method used is the Development of KKN Information System datacollection, analysis, design, implementation and testing. System design uses Data FlowDiagrams (DFD) and ERD (Entity Relationship Diagrams). The development of theKKN information system development using PHP version 5.6.23 and MySQL. Theadded feature is the student registration feature, KKN photo gallery upload feature,input KKN value, message input to LPPM, input announcement and upload fileattached to the announcement. This research facilitates students and LPPM inregistering KKN and group division so that it can be far more effective and efficienKeywords: Application Development, KKN, PHP, MySQL, Web.